2023
DOI: 10.1002/fsn3.3250
|View full text |Cite
|
Sign up to set email alerts
|

Secoisolariciresinol diglucoside and anethole ameliorate lipid abnormalities, oxidative injury, hypercholesterolemia, heart, and liver conditions

Abstract: Fennel seeds and flaxseed have been traditionally used against many medical ailments due to their medicinal characteristics. The aim of the study was to investigate the health properties of secoisolariciresinol diglucoside (SDG) and anethole from flaxseed and fennel seeds in rats fed with high‐fat diet. Histopathological changes in the heart and liver were also examined. Sixty rats were divided into two main groups. Group I (10 rats) was used as a negative control group and fed on the basal diet only. Group II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In this current investigation, consumption of cookies enriched with anethole + SDG restored the lipid profile to normal ranges. Studies have suggested similar effects (Noreen, Rehman, et al, 2023;. An earlier which study found that rats on a high-cholesterol diet with flaxseed oil supplementation had their blood lipid profiles improved was used to support this conclusion (Adolphe et al, 2010;Farook et al, 1991).…”
Section: Plasma Lipidmentioning
confidence: 93%
See 1 more Smart Citation
“…In this current investigation, consumption of cookies enriched with anethole + SDG restored the lipid profile to normal ranges. Studies have suggested similar effects (Noreen, Rehman, et al, 2023;. An earlier which study found that rats on a high-cholesterol diet with flaxseed oil supplementation had their blood lipid profiles improved was used to support this conclusion (Adolphe et al, 2010;Farook et al, 1991).…”
Section: Plasma Lipidmentioning
confidence: 93%
“…The phytoestrogens (flax seed lignans and soy isoflavones) are often found in the human diet. A number of studies employing dietary flaxseeds have been carried out to date, and the results showed that SDG lignan may reduce plasma cholesterol concentrations (Noreen, Rehman, et al, 2023; Nwozo et al, 2023; Zhuang et al, 2021). The purpose of this study was to evaluate the effectiveness of SDG + anethole‐enriched cookies for hyperlipidemic patients having high range of total cholesterol (>220 mg/dL), total triglyceride (>150 mg/dL), and low‐density lipoprotein (>130 mg/dL).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that flaxseed supplementation was tolerated well by the patients and led to exceptional and consistent decreased levels of LDL and total cholesterol. However, it had no significant effects on lipoprotein a, interleukin 6 (IL-6), and C-reactive protein (CRP) (Kanikowska et al, 2020;Noreen, Rehman, et al, 2023; F I G U R E 2 Flaxseeds improve heart health by reducing the progression of atherosclerosis, inflammation, and cholesterol level.…”
Section: Fl a X S Eed And Hyperlipidemiamentioning
confidence: 99%
“…In the late twentieth century, little was understood about the health‐related advantages of flaxseed and how to ingest flaxseed to get any health benefits. The amount of research on the benefits of eating flaxseed has expanded considerably (Brown et al, 2018 ; Noreen, Rehman, et al, 2023 ; Noreen, Tufail, Badar Ul Ain, Awuchi, 2023 ; Noreen, Tufail, Badar Ul Ain, Ali, et al, 2023 ; Noreen, Tufail, Tufail, et al, 2023 ). The bioactive found in flaxseed provide these health benefits in many circumstances, and the forms of flaxseed that are necessary to supply these bioactive to the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation